DIGITALIZING BASED ON TRI HITA KARANA: HOW TECHNOLOGY STRENGTHENS SUSTAINABLE ACCOUNTING FOR MICRO SMALL MEDIUM ENTERPRISE IN DENPASAR - Karninsih, Ni Luh Ayu; Putri, Luh Putu Rina Sari; Putra, Ni Nyoman Ayu Nirmala; Pebrianti, Ni Ketut Enji; Wati, Luh Ade Mirah Anggara; Trirahayu, Ni Komang Yuli; Pratiwi, I Gusti Ayu Angga (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This study examines the integration between digital technology and the local wisdom of Tri Hita Karana (THK) in strengthening sustainable accounting practices among Micro, Small, and Medium Enterprises (MSMEs) in Denpasar. The background of this research is based on the imbalance between the global trend of digitalization and the lack of business models that consider local cultural values. MSMEs in Bali face challenges in implementing sustainability principles, as the approaches used often emphasize technical aspects, while local values such as THK have not been internalized into accounting systems. The main problem in this study is the absence of a sustainable accounting model that holistically integrates digital technology and THK values. This research seeks to answer the question: how can the integration of these two elements enhance the sustainability of MSMEs in Denpasar? The novelty of this study lies in the formulation of a conceptual model that unites three essential aspects, technology, accounting, and local culture, which have previously been studied only in part. The research adopts a quantitative approach, with data collected through questionnaires distributed to MSME owners or managers who met specific criteria. The data were analyzed using SmartPLS 4.0. The findings reveal that both digital technology and THK values have a positive and significant influence on sustainable accounting practices, with a 40% increase in financial reporting accuracy and a 25% reduction in waste. In conclusion, the success of MSME digitalization relies not only on technological infrastructure but also on the acceptance and practice of local cultural values that reinforce accountability and sustainability. These findings highlight the need for digital literacy training based on local cultural values as a relevant strategy in building resilient and sustainable MSMEs in the era of digital transformation.